Digital cinematography : fundamentals, tools, techniques, and workflows - Stump, David (Routledge, 2020)
Today's successful cinematographer must be equal parts artist, technician, and business-person. The cinematographer needs to master the arts of lighting, composition, framing and other aesthetic considerations, as well as the technology of digital cameras, recorders, and workflows, and must know how to choose the right tools (within their budget) to get the job done. David Stump's Digital Cinematography focuses on the tools and technology of the trade, looking at how digital cameras work, the ramifications of choosing one camera versus another, and how those choices help creative cinematographers to tell a story. This book empowers the reader to correctly choose the appropriate camera and workflow for their project from today's incredibly varied options, as well as understand the ins and outs of implementing those options. Veteran ASC cinematographer David Stump has updated this edition with the latest technology for cameras, lenses, and recorders, as well as included a new section on future cinematographic trends. Ideal for advanced cinematography students as well as working professionals looking for a resource to stay on top of the latest trends, this book is a must read.